P141 How effective are high-cost drugs for rheumatoid arthritis beyond the third choice in routine care?. (26th April 2021) - Walker, David; Robinson, Sandra; Barry, Jane; Punter, Phillip; Kearns, Sinead; Goff, Iain
Abstract: Background/Aims   It became apparent at a session at the BSR Annual Conference 2019 that some CCGs restrict the prescription of high cost drugs (HCDs) beyond three drugs for people with rheumatoid arthritis (RA). We were interested to explore the efficacy of HCDs beyond the third choice in our own service. Methods   All patients in our service who are being considered for HCDs, are discussed at a multi-disciplinary team meeting comprising of seven consultants and eight nurses. The HCD decision is recorded in the minutes of the meeting which were scrutinised to identify patients who had received four or more HCDs. We began at March 2017, the launch of JAK inhibitors, in the expectation that few people would have had four HCDs before that time. The medical records were reviewed for the order of HCDs given and for evidence of efficacy and toxicity. The response to each drug choice was graded as: responder; partial responder and failure (primary non-responder or toxicity). Results   From a database of 2, 673 patients with RA, 542 patients were taking HCDs, thirty-two of those had received four or more of these drugs. Eleven of the thirty-two patients had tried four HCDs, seven had received five HCDs, ten patients had six, one patient had seven HCDs, two had tried eight and one patient had received nine HCDs. The response rates for each choice of drug are shown in table 1 . Many patients responded to their fourth, fifth and sixth choice of HCD. If there was a restriction of three HCDs in our service, thirty-three prescriptions for drugs that patients have responded to, would not have been made. Conclusion   Many patients responded to their fourth or subsequent HCD. Thus, there is no clinical justification in restricting the use of HCDs below at least six choices. Additionally, this data suggests that only small numbers of patients are prescribed more than four HCDs. Therefore lifting this limitation would have little cost implication. Disclosure   D. Walker: Honoraria; Gilead Sciences Ltd, Ely Lilly Pharmaceuticals, Pfizer Pharmaceutical. Grants/research support; Gilead Sciences Ltd. S. Robinson: None. J. Barry: Corporate appointments; Gilead Sciences Ltd. P. Punter: Corporate appointments; Gilead Sciences Ltd. S. Kearns: Corporate appointments; Gilead Sciences Ltd. I. Goff: None.